Penerapan Metode BTQ dalam Meningkatkan Kemampuan Menulis Teks Arab Santri Madrasah Diniyah - Asy'Syahid, Muhammad Abdu; Putra, Wahyu Hanafi; Salma, Kunti Nadiyah (Institut Agama Islam Sunan Giri Ponorogo, 2024)
The existence of BTQ programs in educational institutions should be able to assist in the process of reading and writing the Qur'an to students. However, in fact there are still those who have not met the qualifications of the program. this research is at Madin Roudlotul Huda which is located next to the Al Busyro Mosque, namely on Jl. Raden Patah Dukuh Krajan Sukorejo Village, Sukorejo District, Ponorogo Regency, The method in this Community Service uses the ABCD Method to plan the creation of supporting activities. The ABCD (Asset Based Community Development) method is a method that develops existing assets, potential or opportunities to be better managed. Based on the results of observations, it was found that Madin Roudlotul Huda students have diverse Arabic text writing abilities, this program is very good to continue to be applied in every educational institution. The role of mentoring in this activity is very important, because with the assistance of this BTQ program, those who initially did not know the writing of the Al-Qur'an / Arabic could finally find out and add their insights in terms of reading and writing Al-Qur'an verses.